A Competency Model to Help Selecting the Information Security Method for Platforms of Communication by Visible Light (Vlc) - Soto-Gomez, J; Quezada-Llanca, L; Ternero-Saavedra, R; Serey-Araneda, J (Institute of Electrical and Electronics Engineers Inc., 2018)
It is challenging in Security information and Platforms of Communication by Visible Light (VLC), solutions are made to manage the right Security problems. Several solutions have been developed and evolved constantly to meet complex and ever-changing business needs in the world. In the business context, people who are responsible for a project or an organization undergo professional and emotional stress. This research project has developed a new model which can help decision makers evaluating these alternative methods in relation to articulating different types of Security problems, formulating Security criteria, and simulating expectations of adopting the chosen method for Platforms of Communication by Visible Light (VLC). © 2017 IEEE.